Q: How do you simplify 2x plus 5x?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

3x + 7y

18 + 7x - 12 + 5x = ?18 - 12+ 7x - 5x = ?6 + 2x = ?

6x - 2x + 5x - 3First you want to have the x's by theirselves and the numbers by themselvesIt will still be:6x - 2x + 5x - 3Here, you do 6x - 2x.4x + 5x -3Then you combine 4x + 5x.9x - 3Simplified just like that

If there are no equals you can simplify this by collecting all the x values together and use the addition property of signed numbers. 2x+4x-5x+x=2x; 4+3=7. 2x+7 is the simplified statement.

5x + 4 - 3x + 5 + 2x - 9 = 4x

Related questions

5x - 8a + 4a - 2x + a = 3x - 3a

the simplest form of 5x + 3y +2x - 6y is 7x-3y

3x + 7y

5x+2x-3y+y = (5+2)x+(-3+1)y = 7x - 2y

18 + 7x - 12 + 5x = ?18 - 12+ 7x - 5x = ?6 + 2x = ?

3(x+y)

6x - 2x + 5x - 3First you want to have the x's by theirselves and the numbers by themselvesIt will still be:6x - 2x + 5x - 3Here, you do 6x - 2x.4x + 5x -3Then you combine 4x + 5x.9x - 3Simplified just like that

3x^2 + x + 2x^2 = 5x^2 + x

-3

If there are no equals you can simplify this by collecting all the x values together and use the addition property of signed numbers. 2x+4x-5x+x=2x; 4+3=7. 2x+7 is the simplified statement.

5x+2x=7x2x + 5x = 7x

10x2 + 21x - 10 = 10x2 + 25x - 4x - 10 = 5x(2x + 5) - 2(2x + 5) = (2x + 5)(5x -2)